Resisting wh-questions in business coaching - Dionne, Frédérick; Fleischhacker, Melanie; Muntigl, Peter; Graf, Eva-Maria (Frontiers in Psychology, 2024)
This study investigates clients' resisting practices when reacting to business coaches' wh-questions. Neither the sequential organization of questions nor client resistance to questions have yet been (thoroughly) investigated for this helping professional format. Client resistance is understood as a sequentially structured, locally emerging practice that may be accomplished in more passive or active forms, that in some way withdraw from, oppose, withstand or circumvent various interactional constraints (e.g., topical, epistemic, deontic, affective) set up by the coach's question. Drawing on a corpus of systemic, solution-oriented business coaching processes and applying Conversation Analysis (CA), the following research questions are addressed: How do clients display resistance to answering coaches' wh-questions? How might these resistive actions be positioned along a passive/active, implicit/explicit or withdrawing/opposing continuum? Are certain linguistic/interactional features commonly used to accomplish resistance? The analysis of four dyadic coaching processes with a total of eleven sessions found various forms of client resistance on the active-passive continuum, though the more explicit, active, and agentive forms are at the center of our analysis. According to the existing resistance 'action terminology' (moving away vs. moving against), moving against or 'opposing' included 'refusing to answer', 'complaining' and 'disagreeing with the question's agenda and presuppositions'. However, alongside this, the analysis evinced clients' refocusing practices to actively (and sometimes productively) transform or deviate the course of action; a category which we have termed moving around. thus be treated productively as an instrument to work with clients, rather than against them (Safran and Muran, 1996). A growing body of conversation analytic / CA-based research on helping professions (e.g., psychotherapy, counselling) conceptualizes resisting as an interactional phenomenon. Thus, resistance is not an inherent feature of clients, but rather a joint construction between helping professionals and help seekers as they orient to interactional norms and constraints (Muntigl